Efeito de elementos susbstitucionais e intersticiais nas propriedades mecânicas e na biocompatibilidade de ligas do sistema Ti-15Zr-xMo - Correa, Diego Rafael Nespeque [UNESP] (2015)
Titanium and its alloys are used in the biomedical area primarily as cardiovascular, orthopedic and dental implants, due to the high mechanical resistance and density ratio, low modulus of elasticity, excellent corrosion and wear resistance, plus proven biocompatibility. The zirconium presents similar chemical properties to titanium, and can improve the mechanical and corrosion resistance. Molybdenum is a strong β-stabilizer, which can decrease the modulus of elasticity and improve corrosion resistance. In this work we analyzed the effects of alloying elements and thermomechanical treatments in Ti-15Zr-xMo (x= 5, 10, 15 and 20 wt%) alloys, aiming at biomedical applications. The quality of the samples was evaluated by optical spectrometry, EDS, chemical mapping and density measurements. The structural characterization was obtained by DRX measurments and analysis by the Rietveld's method. The microstructural characterization was performed by OM, SEM and TEM. The mechanical properties were analyzed by measures of Vickers microhardness and modulus of elasticity. The chemical characterizations indicate a good quality of alloys for the study. The structural characterization indicated a crystalline structure with a+β phases for Ti-15Zr-5Mo alloy, mestable β phase for Ti-15Zr-10Mo alloy, and β phase for Ti-15Zr-15Zr and Ti-15Mo-20Mo alloys. The microstructural characterization exhibited the formation of a phase in the form of fine acicular structures and β phase as equiaxial grains. The mechanical analysis indicated that the hardness and modulus of elasticity of the alloys were sensitive to the concentration of molybdenum. The microstructure and mechanical properties were analyzed also with interstitical oxygen dependence, moreover, the thermomechanical treatments change significantly the microstructure of alloys. Cytotoxic effects were not observed in any of the studied alloys. The Ti-15Zr-15Mo presented better mechanical compatibility and...